IDENTIFIKASI PENGARUH BENTUK DESAIN BANGUNAN TERHADAP INTENSITAS KONSUMSI ENERGI MELALUI METODE SIMULASI KOMPUTASIONAL SEFAIRA - A'yun, Qurrotul (Department of Architecture, Faculty of Science and Technology, Alauddin State Islamic University, 2023)
Currently, architectural items need to be energy efficient in addition to being aesthetically pleasing and practical. Residential or residential-type objects are not exempt. Residential buildings need to be kept at comfortable temperatures and with appropriate lighting while also being mindful of their energy usage. The importance of energy usage in building design depends on several aspects. These include the building's orientation, the material of the building envelope, the shape of the window, and the building plan and room volume. In order to attain the Energy Consumption Intensity (IKE) value required by the 2012 Regulations of the Ministry of Education and Culture and the Ministry of Energy and Mineral Resources, a suitable form of building design is therefore necessary. Performance-Based Design is one method that could be used to address this issue. A design methodology known as